Pengaruh Product Knowledge, Brand Image, Dan Online Customer Review Terhadap Keputusan Pembelian Di Marketplace Shopee (Studi pada Customer Marketplace Shopee di Malang) - Amalia Fadhila Rakhma; Pardiman Pardiman; Aleria Irma Hatneny (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThe development of shopping behavior online current has made the marketplace Shope very popular with consumers. So that in the buying process it is necessary to pay attention to factors such as product knowledge, brand image, and online customer reviews in order to buy the right product. This study aims to determine the extent of the influence of product knowledge, brand image, and online customer reviews on purchasing decisions in the marketplace Shopee (Study on customers Shopee in Malang). The population of this research is customers Shopeein Malang with a sample of 80 respondents. The sampling technique used simple random sampling. The data collection of this research uses primary data with Google Form. Then the validity and reliability tests were conducted before data analysis was carried out. The results of the F test study indicate that   product knowledge, brand image, and online customer reviews simultaneously have a significant positive effect on purchasing decisions. And the t test states that  product knowledge, brand image, and online customer reviews each have a partially positive and significant effect on purchasing decisions. Keywords        : Product knowledge, brand image, online customer review, purchasing decisions